BIOGRAFI EKONOM ISLAM DAN KONTRIBUSINYA TERHADAP DUNIA PERBANKAN ISLAM SERTA PERAN KRUSIAL PADA SEKTOR PENDIDIKAN DI INDONESIA - Pebriani lubis (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2023)
Abstrac Bigrafi Islamic economists are thinkers in the field of Islamic economics who provide a variety of ideas listed on their minds. These figures also provide many different views or views related to Islamic economics. Here the author only discusses two Islamic economists, namely Ibn Khaldun and Al-Ghazali. Ibn Khaldun is a Muslim historian from Tunisia and is often referred to as the founding father of historiography, sociology and economics. He himself was born in Tunisa on the 1st of Ramadan in 732 H/27 May 1332 AD. Al-Ghazali is one of the great thinkers in the field of Islamic economics. Al-Ghazali himself is a Persian native, he was born in Thus, Khurasan province, Iran in 450 H/1058 AD. The purpose of the author of this journal is to introduce a brief biography of Islamic economics as well as his thoughts in the field of Islamic banking and education. Key Word: Biografi, Perbankan Syariah, Pendidikan.